(untitled) (Slavic Studies, 2025)
The article examines various aspects of the non-trivial existence of the so- called Russian swearing in everyday communication, such as issues of the origin and original semantics of the most ancient words in the Slavic language, as well as the issue of their modern understanding, evaluation and role in the national language. The author believes that in the distant past all the ancient vocabulary, now considered obscene, was common Slavic, sacred and in no way abusive or low. This equally applies to the actual “obscene” expression and to the vocabulary denoting the generative organs of a person. The issue of the functioning of swear words in modern Russian jokes is also considered.